Decoupled Control for Double-T Dc-Dc MMC Topology for MT-HVdc/MVdc Grids - Pesce, Cristian; Riedemann, Javier; Pena, Ruben; Andrade Aguero, Ivan Eric; Jara, Werner; Villalobos, Rodrigo (My University, 2023)
Featured Application The control method proposed in this work can be applied to power converters operating in multi-terminal high-voltage dc systems. This paper proposes a decoupled control of a dc-dc modular multilevel converter (MMC) based on a double-T topology intended for multi-terminal high voltage direct current (MT-HVdc) transmission systems or emerging distribution systems operating in medium voltage direct current (MVdc). The aim of the proposed control strategy is to obtain an input current with reduced harmonic content and to eliminate the output ac common-mode voltage, which is not allowed in MT-HVdc systems. The control strategy consists of injecting two circulating ac currents and two dc currents that allow the energy balance between the arms of the converter and the general energy balance of the topology. The dc and ac currents are decoupled and allow control over load variations and reference changes in the dc-links. The proposed topology is mathematically modeled and the control method is then derived. Simulation results are presented to validate the proposed system.
Keywords: dc-dc power converters; modular multilevel converters; mt-hvdc converters; hvdc grids; mvdc grids